Medical Students’ Knowledge of Fertility Awareness-Based Methods of Family Planning - Danis, Peter G.; Kurz, Sally A.; Covert, Laura M. (Frontiers in Medicine, 2017)
Objective Traditional medical school curricula have not addressed fertility awareness-based methods (FABMs) of family planning. The objective of this study was to assess (1) 3-year medical students’ knowledge of FABMs of family planning, (2) their confidence in utilizing that knowledge in patient care, and (3) to implement focused education on FABMs to improve knowledge and confidence. Methods Third-year medical students at one institution in the United States were given a 10-question assessment at the beginning of their OB-GYN rotation. Two lectures about FABMs and their clinical applications were given during the rotation. Students were given the same questions at the end of the rotation. Each questionnaire consisted of eight questions to assess a student’s knowledge of FABMs and two questions to assess the student’s confidence in sharing and utilizing that information in a clinical setting. McNemar’s test was used to analyze the data. Results Two hundred seventy-seven students completed a pretest questionnaire and 196 students completed the posttest questionnaire. Medical knowledge improved from an initial test score of 38.99% to final test score of 53.57% (p < 0.05). Confidence in sharing FABM information with patients (0 = very uncomfortable; 5 = very comfortable) improved from 1.51 to 3.00 (p < 0.05). Confidence in utilizing FABM to diagnose and treat gynecologic/reproductive problems (0 = not very confident and 5 = very confident) improved from 1.01 to 3.15 (p < 0.05). Conclusion Medical schools may not include FABMs in OB-GYN curriculum; however, to patients, these methods remain a sought after and valid form of family planning. This study shows that brief, focused education can increase medical students’ knowledge of and confidence with FABMs of family planning.